Effect of Tb Content on The Electrical Properties of Double Perovskite Oxide Pr(2-X) Tbxcomno6. (October 2019) - Li, Xiaoxin; Xing, Ru; Zhao, Jianjun
Abstract: Polycrystalline samples of double perovskite oxide Pr(2-x) TbxCoMnO6 (x=0, 0.05, 0.1, 0.15) were prepared by traditional high temperature solid phase reaction. The structure and electrical transport properties of the samples were investigated by the relationship between the XRD lines and the resistivity of the samples ( ρ -T curve). The results show that all the samples show good single-phase, belonging to monoclinic system, space group is P21 /n; the samples are all semiconductor materials; the existence of magnetic field is not conducive to electrical conduction; compared with other samples, the samples with x=0.1 and x=0.15 had better conductivity. The samples in the measured temperature region all follow the way of electrical conduction of variable-range hopping.